Codifying the Doctrine of Unjust Enrichment in Indonesian Law of Obligations - Arsyad Y. Idrus (SEAN Institute, 2026)
This article examines the normative and systematic urgency of codifying the doctrine of unjust enrichment within Indonesia’s law of obligations. Although Indonesian private law, rooted in the civil law tradition, has long recognised contract and tort as the principal sources of obligations, it lacks an explicit and autonomous framework governing situations where one party is enriched at the expense of another without sufficient legal ground. This doctrinal gap forces courts to rely on broad principles of equity, good faith, and analogical reasoning, or to stretch contractual and delictual concepts beyond their proper domains, thereby undermining legal certainty, consistency, and equal treatment. Using a normative juridical method, supported by comparative analysis of developed unjust enrichment regimes in other jurisdictions, this research argues that codification is necessary to complete the triadic structure of obligations, clarify the relationship between unjust enrichment, contract, and tort, and provide clear elements and limits for restitutionary claims. Codification is further justified by the increasing complexity of modern transactions, particularly in the digital and financial sectors, where enrichment without legal basis frequently arises outside traditional fault‑based or consent‑based categories. The study concludes that an explicit unjust enrichment regime would enhance substantive justice, strengthen doctrinal coherence, and affirm the role of Indonesian private law as a credible instrument for regulating the fair distribution of gains and losses.